Lobular carcinoma in situ - A pragmatic approach to the controversies - Jane Brock (Elsevier, 2022)
We lack consensus guidelines for management of pleomorphic and florid LCIS (PL- and FL-LCIS), resulting in ad hoc management of patients, both within and across institutions. This review discusses current definitions, variants, and management controversies. LCIS with necrosis should be included in the definition of FL-LCIS, and an inflammatory infiltrate associated with LCIS or with extracellular mucin production, are higher-risk variants. If we define our treatment goal in terms of crude annual recurrence at 1% per year, in line with DCIS recurrence goals, we can standardize treatment to achieve this, and assess the outcomes over time across multiple institutions. Based on published PL-LCIS studies, guidelines should include obtaining negative margins (no-tumor-on-ink), as positive margins are more frequently seen in cases of recurrence (38.4% vs 22.8% for all cases). Testing PL-LCIS for Estrogen Receptor (ER) can be recommended to guide chemoprevention decision-making (given a 21% ER negative rate). HER2 status in both PL- and FL-LCIS (14% and 6% positive respectively) can help inform treatment decisions (e.g. favor DCIS-style management if positive), because unlike DCIS, treatment of LCIS is not uniform. Finally, a recommendation for or against radiation therapy in the setting of breast conservation, for PL-LCIS and FL-LCIS would also clearly establish its utility over time.